(untitled) (Sinología hispánica. China Studies Review, 2021)
Based on the panel data of 75 commercial banks in China from 2008 to 2017, this paper uses four methods: mixed estimation, fixed effect, differential moment estimation and system moment estimation, to examine the impact of leverage ratio regulation on commercial bank risks and the influence of heterogeneity of commercial banks on regulatory effectiveness. We found that, first, the supervision of leverage ratio effectively reduces the risks of Chinese commercial banks; second, the heterogeneity of Chinese commercial banks will lead to differences in regulatory effects. For banks that are listed with lower capital levels and have higher risk preference, leverage ratio regulation has a stronger inhibitory effect on bank risks. On this basis, it is recommended that the regulators implement differentiated supervisory measures for commercial banks with different capital levels and risk reference while strengthening supervision of leverage.